Helen Keller : A Photographic Story of a Life. - Garrett, Leslie (New York, NY : DK Publishing Company, 2004)
A photographic story of the life of Helen Keller.
Keywords: Helen Keller - Biography - Juvenile Literature; Braille - Juvenile Literature; Teaching the Blind - Juvenile literature